(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
The article attempts to describe the development of the negotiations between the Colombian government of President César Gaviria (1990-1994) and the representatives of each of the insurgent groups that formed the Simón Bolívar Guerrilla Coordination between 1991 and 1992, a period in which a series of meetings were held in Venezuela and Mexico with hopes of seeking a negotiated solution to the armed conflict. With this, the aim is to analyze the negotiating process with all the Colombian armed organizations